PENGEMBANGAN E-MODUL BERBANTUAN SMART APPS CREATOR PADA MATERI BANGUN RUANG SISI DATAR TINGKAT SMP - Mutaqinah, Tiara Amalia; Nurjanah; Dinny Mardiana (Universitas Islam Nusantara, 2024)
This research is motivated by technological developments that require educators to have the ability to adapt, adapt, and be creative in carrying out the learning process and mathematics subjects which are always considered difficult and boring by some students because of their abstract nature. Therefore, it is necessary to have interactive learning media in the form of e-modules in order to help students understand abstract mathematics learning. This study aims to develop electronic modules (e-modules) assisted by valid smart apps creators. The approach used in this study is a qualitative approach. The method used is Research and Development (R&D) with the ADDIE design (Analyze, Design, Development, Implementation, and Evaluation). The subjects in this study were class VIII students and one of the mathematics educators at MTs Darul Hufadz. The data collection instruments used were validation sheets, student questionnaires and educator questionnaires. The results of the data validation analysis obtained by material experts and media experts, the two experts obtained very valid categories. The results of practicality after using the e-module according to students are in the practical category